Thermal stabilisation of squaraine dyes by encapsulation in a rotaxane. (24th November 2020) - Bak, Helle Ø.; Nielsen, Bjarne E.; Petersen, Michael Å.; Jeppesen, Anne; Brock-Nannestad, Theis; Nielsen, Christian B. O.; Pittelkow, Michael
Abstract : Encapsulation of a squaraine dye in a rotaxane structure renders the dye that normally start decomposing at 100 °C stable above 250 °C. This thermal stabilisation makes new applications possible, and we demonstrate how the squaraine rotaxane can mediate laser welding of polyethylene. Abstract : Here we show how encapsulation of a squaraine dye in a rotaxane structure renders the dye that normally start decomposing at 100 °C stable above 250 °C. This thermal stabilisation makes new applications possible, and we demonstrate how the squaraine rotaxane can mediate laser welding of polyethylene, a process that requires thermal stability.